Evidence of in-situ Cu clustering as a function of laser power during laser powder bed fusion of 17–4 PH stainless steel. (October 2022) - Moyle, M.S.; Haghdadi, N.; Davids, W.J.; Liao, X.Z.; Ringer, S.P.; Primig, S.
Abstract: The use of intrinsic heat treatments to control the microstructural evolution during additive manufacturing could eliminate the need for costly post-build processing. Using atom probe microscopy and cluster search algorithms, this study investigates the degree of Cu clustering and precipitation in 17–4 precipitate hardening (PH) stainless steel fabricated by laser powder bed fusion (LPBF). It was found that LPBF samples exhibit a greater than random degree of Cu clustering, irrespective of the laser power during fabrication. It is further shown that using a higher laser power (161.5 W rather than 127.5 W) led to a higher number density of Cu clusters, Cu precipitates, and higher hardness due to the greater heat input. The observations of Cu-rich clusters and precipitates within as-printed LPBF samples and its laser power dependence are novel and show potential for inducing desired strengthening phases directly during LPBF, mitigating the need for post-fabrication heat treatments. Graphical abstract: Image, graphical abstract